Observability of food safety losses in maize: Evidence from Kenya - Hoffmann, Vivian; Mutiga, Samuel H.; Harvey, Jagger; Nelson, Rebecca J.; Milgroom, Michael G. (International Food Policy Research Institute, 2019)
Unlike physical losses, deterioration of food safety can be difficult to observe. In low- and middle- income countries, much of the food supply is never tested for safety hazards. We analyze data from 1500 maize samples and associated consumer surveys collected from clients of small-scale hammer mills in rural Kenya. We find that while visible damage to maize is penalized by lower prices, there is no correlation between price and aflatoxin, a carcinogenic fungal contaminant, implying an absence of market incentives to manage this aspect of food loss. Aflatoxin contamination is, however, correlated with consumer perceptions of quality, especially for self-produced maize, suggesting an information asymmetry that could lead to inefficiencies in this market.